Representations of Still Life in Chinese Painting of the First Half of the 20th Century: The Shanghai School - Rybalko, Svitlana; Zhang, Zhe (HUDPROM: The Ukrainian Art and Design Journal, 2023)
The purpose of the article is to determine the ways of formation of still life as a genre in the first half of the 20th century and the features of its conceptualization; highlighting the creative output of representatives of the Shanghai school in the field of depicting the objective world. A wide range of visual materials is considered, and a circle of representatives of the Shanghai school who participated in the development of still life as an independent genre of painting is identified. Wu Changshu and Qi Baishi are among the most significant creators of still life. Representative samples and leading approaches to the development of the figurative structure of still life, its understanding as a complete symbolic and artistically expressive composition, as a gift and expression of an individual creative principle are identified. The connection of the Shanghai still life with the previous tradition is shown, and the decisive influence of wenrenhua aesthetics is highlighted; the significance of Shanghai as an artistic center and a cosmopolitan environment for the development of the artistic process is pointed out. It is emphasized that the still life of the Shanghai school became a transitional link to the still life of the Western style. The cultural status of still life as a result of the activity of scientists determined its perception by Japanese artists, the representatives of the Nanga school and ensured its further spread in the art of China, Japan and Korea. The main approaches to the interpretation of pictorial motifs close to still life are determined. Traditional and modern aspects in the depiction of the objective world by representatives of the Shanghai school in the first half of the 20th century are identified. The practical significance of the research results lies in the possibility of their use in the development of the conceptual framework for educational courses, textbooks, as well as in artistic and museum practices.